Role functioning among adults with schizophrenia. (March 2015) - Westcott, Cassandra; Waghorn, Geoff; McLean, Duncan; Statham, Dixie; Mowry, Bryan
Introduction: The extent that adults with schizophrenia and schizoaffective disorders participate in socially valued roles within their community is an important aspect of recovery and rehabilitation. Although previous research has explored functioning in specific roles (for example, education, employment and independent living) less is known about combined participation in different types of socially valued roles. The purpose of this investigation was to describe the role functioning of a community sample of 255 adults with schizophrenia or schizoaffective disorder. Method: The diagnostic interview for genetics study 2.0 was administered by trained clinicians and provided the background clinical information for this report. A subsample from the genetics study was interviewed by telephone using the socially valued role classification scale. Participants were specifically asked about their participation in employment, education and training, rehabilitation, caring for others, and home duties and self-care. Results: Overall role participation was high, with 80% participating in socially valued roles other than independent living. Role functioning in each role category was relatively independent of functioning in other role domains. Conclusion: Occupational therapists can best facilitate the rehabilitation and recovery of community residents with severe mental illness by adopting a role-specific approach based on individual preferences for particular role domains.